2012
DOI: 10.1111/j.1365-2826.2011.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Localisation of Kisspeptin with Galanin or Neurokinin B in Afferents to Mouse GnRH Neurones

Abstract: The gonadotrophin-releasing hormone (GnRH) secreting neurones, which form the final common pathway for the central regulation of reproduction, are directly targeted by kisspeptin (KP) via the G protein-coupled receptor, GPR54. In these multiple labelling studies, we used ovariectomised mice treated with 17β-oestradiol (OVX + E(2)) or vehicle (OVX + oil) to determine: (i) the ultrastructural characteristics of KP-immunoreactive (IR) afferents to GnRH neurones; (ii) their galanin or neurokinin B (NKB) content; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 99 publications
5
78
1
1
Order By: Relevance
“…The ARN kisspeptin, or KNDy cells, synthesize numerous neuropeptidergic and classic transmitters (20,23,35) and innervate only the distal processes of GnRH neurons in mice, either at the level of the dendron or their nerve terminals in the median eminence (36,37). We found that 2-Hz stimulation of ARN KNDy neurons was completely ineffective in modulating LH secretion.…”
Section: Discussionmentioning
confidence: 75%
“…The ARN kisspeptin, or KNDy cells, synthesize numerous neuropeptidergic and classic transmitters (20,23,35) and innervate only the distal processes of GnRH neurons in mice, either at the level of the dendron or their nerve terminals in the median eminence (36,37). We found that 2-Hz stimulation of ARN KNDy neurons was completely ineffective in modulating LH secretion.…”
Section: Discussionmentioning
confidence: 75%
“…Alignment of peptide sequences reveals some sequence similarity among the three peptide groups, with SPX more closely related to galanin, and ligand-receptor interaction studies revealed that SPXs activate human GAL 2/3 but not GAL 1 , suggesting they may be natural ligands for GAL 2/3 . Furthermore, SPXs exhibited higher potency at GAL 3 than galanin (Kim et al, 2014), suggesting a possible role in endogenous regulation of GAL 3 signaling that should prompt further experimentation, particularly in relation to reproduction (e.g., Porteous et al, 2011;Kalló et al, 2012).…”
Section: Final Considerationsmentioning
confidence: 99%
“…In addition to the neuronal actions of galanin already discussed, there are many other actions that, because of space restrictions, cannot be covered in detail. These include roles in arousal and sleep regulation (see Gaus et al, 2002;McGinty and Szymusiak, 2003;Saper, 2006), reproduction and associated behavior, neuroendocrine mechanisms, and hormone release, which are reviewed elsewhere, along with similar GALP actions (see, e.g., Gundlach, 2002;Gottsch et al, 2004;Crown et al, 2007;Kalló et al, 2012; see section VI).…”
Section: Galanin Family Peptides and Receptorsmentioning
confidence: 99%
“…One possibility is that Kiss1r normally signals on the ciliary membrane and ciliary localization concentrates the receptors to optimize ligand binding and signal propagation. There is evidence for both synaptic (41,42) and volume (43) transmission of kisspeptin to GnRH neurons. Ciliary response to ligand should be involved in volume transmission as cilia project from the cell body and synaptic contacts have never been observed on neuronal cilia.…”
Section: Discussionmentioning
confidence: 99%